Dieter Rams : as little design as possible - Lovell, Sophie, ....-; Ive, Jonathan, ....- (London : Phaidon, 2011)
Indifference towards people and the reality in which they live is actually the one and only cardinal sin in design' - Dieter Rams. Dieter Rams' life and work are indelibly linked to his thoughts about how people live, and how they can live better. Products he designed in the 1960s are still being produced and sold today - only one demonstration of the strength of his work. This comprehensive monograph covers both Rams' life and his work, as well as his ideas on good design, which continue to inspire designers and consumers today. A personal foreword by Jonathan Ive evokes the influence that Rams has had on his own work and, by extention, the objects with which so many of us share our everyday lives. An introduction and an essay by Klaus Kemp tell the story of Rams' early life, his training as an architect, and the intellectual context in which his ideas were developed.
Includes bibliographical references and index.
Keywords: Rams, Dieter, -- 1932-.; Industrial design -- History -- 20th century -- Germany